The Impact of Cross-Cultural Management on Global Collaboration and Performance - As’ad, Ajmal; Junaidin, Junaidin; Syarifuddin, Syarifuddin; Herison, Roni; Syukur, Abdul (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
This study examines the impact of cross-cultural management on global collaboration and organizational performance in multinational corporations (MNCs). It focuses on how effective cross-cultural management practices enhance team collaboration, communication efficiency, and leadership adaptability. Data were collected through surveys and interviews with employees and leaders from various MNCs. Quantitative analysis was performed on survey responses to identify correlations between cross-cultural management practices and organizational performance metrics. Qualitative insights from interviews provided additional context and depth. The findings indicate that cross-cultural management significantly enhances team cohesion and communication efficiency. Employees who underwent cross-cultural training reported higher levels of collaboration and fewer misunderstandings. Leadership adaptability emerged as a crucial factor, with culturally intelligent leaders effectively managing diverse teams. The study also revealed that cross-cultural management contributes to higher innovation and organizational performance. The study underscores the importance of investing in cross-cultural training and developing culturally intelligent leadership. Organizations should implement comprehensive training programs and inclusive policies to leverage cultural diversity. These practices improve interpersonal relations and lead to tangible business benefits, including higher employee satisfaction and productivity.